3D printing of PTFE-filled polyimide for programmable lubricating in the region where lubrication is needed. (March 2022) - Yao, Xinle; Sen Liu,; Ji, Zhongying; Guo, Rui; Sun, Chufeng; Guo, Yuxiong; Wang, Xiaolong; Wang, Qihua
Abstract: Three-dimensional (3D) target-region-lubrication printing of photosensitive polyimide (PSPI) filled with polytetrafluoroethylene (PTFE), i.e., PSPI-PTFE, with excellent tribological properties for self-lubricating devices was realized by digital light processing of PSPI-PTFE ink and thermal post-treatment. The 3D-printed PSPI-PTFE composites exhibited the friction coefficients and wear rates sharply reduced by 88% and 98%, respectively, and good mechanical properties, thermal stability and interlayer bonding as well. Importantly, the surfaces with lubricating only in regions where needed were readily realized due to the layer-by-layer manufacturing manner of 3D printing. As proof-of-concept, a target-region-lubricating bearing was demonstrated successfully, which run stably with a speed ranged from 60 to 180 rpm/min, indicating that the 3D-printed PSPI-PTFE composites are suitable for fabricating devices with complex and special shapes. Graphical Abstract: ga1 Highlights: Polytetrafluoroethylene (PTFE)-filled photosensitive polyimide (PSPI) was fabricated by vat polymerization 3D printing. The 3D-printed PSPI-PTFE composites exhibited excellent self-lubricating and antiwear properties. The 3D printing of PSPI-PTFE realized surfaces and devices with lubricating PI programed only in regions where needed.